Digital Radio Technologies for Better Mobile Services (Global Journal of Computer Science and Technology, 2013)
Digital mobile communications is one of the great success stories of recent years, offering people levels of mobility and services never available before. The new 3G services will push mobile even further, opening up opportunities for true broadband mobile services. This is not the end of the road for mobile, however. On the contrary, we are still only at the beginning of the mobile revolution. Already the requirements for the next generation of mobile and wireless communications technology are emerging. Future systems must put user needs centre stage - seamlessly integrating the many different communication systems we see emerging today so as to deliver personalised enhanced services to users. In addition, they will require open interfaces and architectures to allow different players to inter-work and offer new services. Such an open approach will be essential for players to compete in a market where users are increasingly mobile and their requirements continually changing. Digital rights management and content management will also be important considerations.
Keywords: digital mobile communication; 3G services; mobile and wireless networks; winner